Common Stochastic Volatility in International Real Estate Market - Wang, Yongsheng; Fadiga, Mohamadou L. (Journal of Reviews on Global Economics, 2014)
This study examined the real estate markets of Europe, North America, and Asia using daily continental real estate indices. It applied a multivariate stochastic volatility model to analyze the behavior of volatility trends in these markets. The results showed comovements in volatilities, especially between Europe and North America, as indicated by high degrees of correlation of their respective stochastic trend components. However, the impact of this common trend varies in these markets, especially for the early period of the sample. For the later period of the sample, the derived volatility trend indicated volatility convergence among them. It might imply that the role of emerging market such as Asia in diversifying real estate investment risk was not as significant as showed in early studies and is diminishing overtime.